Bargaining to Lose the Global Commons - Natasha Chichilnisky-Heal; Graciela Chichilnisky (Fondazione Eni Enrico Mattei (FEEM), 2015)
In "Bargaining to Lose: The Permeability Approach to Post Transition Resource Extraction" [1] Natasha Chichilnisky-Heal introduces an original and fertile explanation for the resource curse. Her "permeability" approach questions the treatment of the state as a decision maker having the public good as an objective, and replaces it by the results of a bargaining game between the state and International organizations. Her new theory is illustrated with unique hands-on experience in the case of copper and gold mines in Mongolia and Zambia, and focuses on a bargaining game between the state and key financial organizations: the Bretton Woods Institutions (IMF, World Bank) and MNCs. This piece extends and generalizes "Bargaining to lose" providing economic models that validate the original conclusions, and exploring its implications for the global commons: the atmosphere, the oceans and biodiversity. Chichilnisky-Heal's "permeable state" is a transition to a new globalized society where the sovereign state - a relatively recent creation - is receding giving rise to a new set of global economic agents and institutions that better explain the dynamics of the global commons. We show that the permeable state complements other explanations for the resource curse [2] as a global market failure magnified by globalization and based on the lack of well-defined property rights on natural resources during the pre-industrial period. We generalize Chichilnisky-Heal's "bargaining to lose" approach to the resource curse and explore its natural implications for the environmental crisis on the global commons. The solutions that Chichilnisky-Heal proposes, e.g. limiting the Bretton Woods' Institutions' `seat at the negotiation table' of resource extraction contracts, could help resolve the environmental crisis that is based on over-extraction of global resources.
Keywords: C70; C78; 330; Bargaining; Global Commons